Holocaust denial, Le Vicaire, and the absent presence of Nadine Fresco and Paul Rassinier in Jorge Semprún's La Montagne blanche. (August 2022) - Reid, Donald
The importance to Jorge Semprún of confronting Holocaust denial in Vichy Syndrome France is not central to analyses that have been done of La Montagne blanche . To detect it, we must do what Semprún never stops asking readers to do: visit the external worlds to which his text directs us and reread his corpus so as to return with new insights and questions to pose to the text at hand. This essay examines La Montagne blanche in light of Semprún's presentation of Jewish characters in Le grand voyage ; his adaptation of Rolf Hochhuth's Le Vicaire ; his critique of the Communist party's belated acknowledgment of the gulag; his relationships to the Holocaust denier and severe critic of the Communists at Buchenwald, Paul Rassinier, and to Nadine Fresco, the most penetrating analyst of Rassinier; and his attention to Holocaust denial when he wrote fiction rooted in historical situations. Holocaust denial is an erasure. La Montagne blanche draws our attention to that erasure in a novel in which the subject is hardly mentioned.